180k views
1 vote
P(0)
17. If p (m) = 4m3 + 3, the value of
p(1)-P(-1)
divides it int

1 Answer

2 votes

Answer:


p(1) - p(-1) =8

Explanation:

Given


p(m) = 4m^3 + 3

Required


p(1) - p(-1)

First, we calculate p(1)

Substitute 1 for m in
p(m) = 4m^3 + 3


p(1) = 4(1)^3 + 3


p(1) = 4*1 + 3


p(1) = 4 + 3


p(1) = 7

Next, we calculate p(-1)

Substitute -1 for m in
p(m) = 4m^3 + 3


p(-1) = 4(-1)^3 + 3


p(-1) = 4*-1 + 3


p(-1) = -4 + 3


p(-1) = -1


p(1) - p(-1) is then calculated as:


p(1) - p(-1) = 7 - (-1)


p(1) - p(-1) = 7+1


p(1) - p(-1) =8

User Dvoyni
by
5.9k points